Comprehensive Review on Fresh and Hardened Concrete Containing Coal Bottom Ash as Sand and Cement Replacement - Narani, Mohd Zulfikar; WAN IBRAHIM, PROF. MADYA Ts. Dr. MOHD HAZIMAN (Recent Trends in Civil Engineering and Built Environment, 2021)
The related significant manufacture of Ordinary Portland cement (OPC) and huge concrete production have been experiential causing a lot of bad impact to the environment. The lack of alternative materials for cement has resulted in a large amount of CO2 being produced and a high energy consumption, all of which are the consequences of cement manufacturing. One type of solid agricultural waste was adopted in this research, namely Coal bottom ash (CBA) as fine aggregate and cement replacement in different proportions, respectively. The different percentage of CBA by different reference was used as a partial replacement of fine traditional fine aggregate and as a partial replacement of ordinary Portland cement (OPC). This paper summarized numerous vibration response studies of the fresh and hardened properties of the concrete incorporating CBA as sand and cement replacement. The effect of various parameter on fresh and hardened properties such as the density, workability, compressive strength, tensile strength, microstructure and water absorption in concrete containing CBA as sand and cement replacement was studied and discussed in detail by classification. Finally, on the summary table of the previous study was noted, presenting the parameter studied and remarks on each study conducted. The optimum percentage of CBA to replace cement and sand effect of the properties of the concrete will be determined